Addendum zu Chlorierte Biphenyle [BAT Value Documentation in German language, 2019]. Issue 2 (25th April 2019) - Brinkmann, B.; Bartsch, R.; Schriever‐Schwemmer, G.; Drexler, H.; Hartwig, A.; ,
Abstract: In 2018 the German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area evaluated the possibility to add the indication "prerequisite for Pregnancy Risk Group C" for chlorinated biphenyls. Chlorinated biphenyls are classified in Pregnancy Risk Group B because adhering to the biological tolerance value (BAT value) of 15 µg/L plasma for the sum of the indicator congeners PCB 28, PCB 52, PCB 101, PCB 138, PCB 153, PCB 180 cannot exclude a risk to the developing foetus. This classification was mainly based on developmental neurotoxicity and reduced birth weight in monkeys exposed to mixtures of chlorinated biphenyls. In this re‐evaluation, numerous environmental epidemiological studies on developmental effects and birth weight and extensive reviews of these studies are taken into account. These studies show that the critical effect in humans is developmental neurotoxicity, for which a NOAEL of 3.5 µg/L plasma for the sum of the 6 indicator congeners can be derived. Therefore, an internal exposure not higher than this concentration would be the prerequisite for an assignment to Pregnancy Risk Group C, which means that damage to the embryo or foetus is unlikely at this concentration.